Rathke's cleft cysts. - Trifanescu, R; Ansorge, O; Wass, J; Grossman, AB; Karavitaki, N (2012)
Rathke's cleft cysts (RCCs) are benign, sellar and/or suprasellar lesions originating from the remnants of Rathke's pouch. Although a common finding in routine autopsies (12-33% of normal pituitary glands), symptomatic cases are rare and comprise 5-15% of all surgically resected sellar lesions. Small, asymptomatic RCC do not require surgical intervention, and their natural history is not clear. In series of nonoperated presumed RCCs, 26-94% did not progress during follow-up periods up to 9 years. In symptomatic ones, surgery is indicated, aiming to drain the cyst content and safely remove as much of the capsule as possible. Following surgical intervention, headaches and visual field defects improve or resolve in a significant number of patients (40-100% and 33-100%, respectively) and partial hypopituitarism recovers in 14-50%. Data on relapse rates published in the last 15 years are based on variable follow-up periods and show wide variation (between 0% and 33%). The lowest relapse rates have been described in reports with relatively short mean observation periods (<3 years), whereas in those with longer follow-up the relapse rates increase. Most of the relapses occur within 5-6 years, suggesting that follow-up is required for at least 5 years after surgery. Risk factors for relapse include the presence of squamous metaplasia in the cyst wall, cyst size and the presence of inflammation. Long-term sufficiently powered studies aiming to clarify the natural history of asymptomatic RCCs and of those relapsing postoperatively are required.